Cyber Crime in Pakistan: Trends, Challenges, and Legal Responses: https://doi.org/10.55966/assaj.2025.4.1.080 - Asad U Allah Khan (`, 2025)
Cybercrime in Pakistan has emerged as a critical challenge, threatening economic stability, social harmony, and national security. This article examines the current trends, key challenges, and legal responses to cyber threats in Pakistan, offering a comprehensive analysis of the evolving digital landscape. The study highlights prevalent cybercrimes, including financial fraud, identity theft, cyber harassment, and data breaches, alongside emerging threats like ransomware, deepfake technology, and cyberterrorism. Despite legislative measures such as the Prevention of Electronic Crimes Act (PECA) 2016, systemic gaps in enforcement, technological infrastructure, and public awareness persist. The article identifies three major challenges: technical limitations (outdated cybersecurity systems, low digital literacy), institutional weaknesses (slow judicial processes, jurisdictional hurdles), and socio-cultural barriers (underreporting due to stigma, lack of victim support). Case studies of high-profile cyber incidents, such as banking fraud and social media blackmail, illustrate the real-world consequences of these vulnerabilities. The analysis concludes with actionable recommendations, emphasizing the need for government-led initiatives (strengthening law enforcement, fostering public-private partnerships), corporate and individual responsibility (adopting cybersecurity best practices, improving reporting mechanisms), and legal reforms (updating PECA, expediting cybercrime trials). Ultimately, this research underscores the urgency of treating cybersecurity as a national priority. By implementing a multi-stakeholder approach combining policy upgrades, technological investments, and public awareness campaigns Pakistan can mitigate cyber risks and secure its digital future. The findings advocate for immediate action to bridge existing gaps and build a resilient cyber ecosystem. Keywords: Cybercrime, Pakistan, PECA 2016, Cybersecurity, Financial Fraud, Cyber Harassment, Ransomware, Deepfake, Cyberterrorism, Legal Reforms, Digital Literacy, Public-Private Partnerships